Сonsolidation of bimetallic nanosized particles and formation of nanocomposites depending on conditions of shock wave compaction; Russian Physics Journal; Vol. 60, No. 7 - Vorozhtsov S. A. Sergey Aleksandrovich; Kudryashova O. B. Olga Borisovna; Lerner M. I. Marat Izrailyevich; Vorozhtsov A. B. Aleksandr Borisovich; Khrustalyov A. P. Anton Pavlovich; Pervikov A. V. Alexander Vasilyevich (2017, 2017)
Title screen